The Amish wanderer - Hilton, Laura V., 1963- (Whitaker House, 2017)
"Desperate for a Ticket Out Bethany Weiss is ready to leave town. Tongues haven't stopped clacking in Jamesport, MO, since her daed, the bishop, was admitted to a mental hospital after hurting their small Amish community. But her sharpest wounds Bethany hides from prying eyes, quietly biding her time until she can take a chance at a new life--away from Jamesport and away from God. Silas Beiler was kicked out of his own family's home. Dogged by a rough childhood and a family who blames him for each new disaster, he begins hitchhiking across the country, sleeping in barns where he can, working for food when possible--headed for Pennsylvania, in the hope of some stability. When Bethany spies a man asleep in the hayloft, she first fears the return of an unwelcome suitor. But when it is Silas who turns and speaks, the memories flood back: a happy summer six years ago full of lemonade, long walks, and budding courtship. Now, however, those months of bliss seem naïve and idyllic. Will their old love overcome new pain? Or will hurt and rejection continue to haunt their path?"--